MOUNTAINS, RIVERS, LAKES OF THE UNITED KINGDOM (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
This article provides a comprehensive overview of the diverse natural landscapes found within the United Kingdom, focusing on its mountains, rivers, and lakes. It highlights the distinctive features of each geographic element, emphasizing their beauty and significance within the UK's natural heritage.